Simultaneous determination of 4-(oxiran-2-ylmethoxy)-9H-carbazol and 2-(2-methoxyphenoxy)ethylamin in carvedilol tablets by HPLC - Tiến, Nguyễn Hữu; Anh, Hồ Ngọc Lan (Hue University Journal of Science: Natural Science, 2020)
Carvedilol is widely used in the treatment of cardiovascular diseases such as hypertension, ischemia, or heart failure. US pharmacopoeia 41 limits the allowable levels of nine related compounds of carvedilol in tablets. Among them, compound D (4-(oxiran-2-ylmethoxy)-9H-carbazole) and E (2-(2-methoxy phenoxy)ethylamin) are the synthetic materials for carvedilol, which appear in raw material and tablets. This research aims to develop a simple method for the determination of these two compounds in the tablets by using high-performance liquid chromatography (HPLC). The HPLC conditions were optimized as follows: Zorbax Eclipse XDB-C8 column (150×4.6 mm, 5 µm); mobile phase: acetonitrile and phosphate buffer (pH 2 + 1-heptanesulfonic acid 1.5 mM) (50:50, v/v); wavelength: 220 nm for compound E and 240 nm for compound D. This method was validated according to The International Conference of Harmonization guideline, and it can be used for the simultaneous determination of compounds D and E in the tablets.